Dredging on water bodies and margin interventions: effects on fish - Thais Aparecida Soinski; Camilla de Souza Gato; Anderson Arimura Matsumoto; Midiã Lima Brazão; Welber Senteio Smith (Boletim do Instituto de Pesca)
The urbanization process deeply affects rivers and streams, with numerous impacts, such as the discharge of sewers, dams, and pipework, causing profound changes in the water bodies characteristics and in their biota. In this scenario, the silting of rivers suffers one of the most impactful changes, as it undergoes a reduction in the depth and width of the rivers, triggering physical and chemical changes in the water, as well as in the structure of fish population, its feeding and reproduction habitats. As a palliative measure, it is normal to carry out the desilting (dredging) of rivers, an activity that is also very impacting. Floodings are one of the main factors that demand dredging to be carried out. This review was made to analyze desilting activities, their effects on biota and migratory fish, as well as to evaluate the best management strategies and mitigation of impacts on fish population. The shifting and removal of sediment from the riverbed can cause burial and massive death of eggs and larvae, in addition to interfering in the upward and downward migration of eggs, larvae, and adults of migratory fish. In addition, breeding and feeding sites can be impacted by sediment movement, dredging, and deposition. Some actions minimize the impacts of the silting activity recovering riparian forests, inspect the use of soil on the banks, move urban settlements away, assess the dredging site, consider the spawning sites and reduce the suspension of bottom sediments, as well as choose the best equipment and time for the performance of activities. Therefore, the development of research on the effect of dredging of water bodies on fish would contribute to a better management of the activity.